Trajetória do teatro experimental do negro: uma busca por novos caminhos comunicacionais - Silva, Jackson Douglas Leal (2018)
This present thesis according to cultural studies in their contemporary line of thought. The aim of this study is implementing anti-racist politics from a critic and conceptual about communicative process actualized by the Teatro Experimental do Negro (TEN). Created in 1944 from Rio de Janeiro city by Abdias Nascimento (1914-2011) the TEN is categorized as a political-aesthetic and artistic organization that developed actions as a mechanism for valuing Brazilian black culture and person. Our hypothesis is based by the idea that the TEN created mechanisms for the black population to articulate and create means to be present in theatrical stages, in academic productions, in the labor market, in social life, as well as to affirm their racial identity; this makes us use the following question: what would be the body and black corporeity, working from the TEN, if not a receptacle of subversion and transgression to the situation of the black person in the theatrical and social scenario of the time? In this sense, through social cartography and documentary analysis, we search to achieve one of the central objectives of the work, which is to understand how the TEN initiatives, marked by confrontation with the hegemonic aesthetics and valorization of culture, black and AfroBrazilian identity, contributed to reorient socio-spatial trajectories in Brazil. In this way, we study social cartography as a mechanism of speech of the subalternized person, socio-spatial trajectories as a movement of exchange of affections and how these lines cross in the search for an affected theory. We also reflect on the possibility of thinking about citizenship in construction, as well as the social mediations made possible by theatrical art. We also bring to the debate the discussion on racism and anti-racism from Abdias Nascimento’s exile; we also considered the possibility and suggestion of an anti-racist agenda for the Brazilian black population.